Bio-mediated detoxification of heavy metal contaminated soil and phytotoxicity reduction using novel strain of Brevundimonas vancanneytii SMA3 - Ankita Ghosh; Diksha Sah; Moumita Chakraborty; J.P.N. Rai (Heliyon, 2023)
Heavy metals pose a serious environmental threat on a global scale due to their toxicity towards livings. Therefore, removing harmful metals from the environment has become more challenging in recent years. The objective of this study is to isolate, examine, and characterize naturally existing bacteria that possess the ability to mitigate and detoxify heavy metals such as cadmium, mercury, and lead. The selected bacteria SMA3 actively demonstrated metal tolerance during screening and was then employed for biosorption study using a lab-scale technique. The bacterium belonged to Brevundimonas sp., according to 16 S rRNA analysis. To enhance the removal efficiency of SMA3, response surface methodology (RSM) was employed, resulting in the identification of optimized conditions (pH 7, temperature 30 °C and shaking speed 120 rpm) for achieving maximum removal percentage (69.5 % of Cd, 58.6 % of Hg, and 85.1 % of Pb) within 72 h. The structural changes induced by microbial treatment were demonstrated by comparing the findings of FESEM images and FTIR spectra confirming the disappearance of C ^ C, C]O peaks along with C]O, C–O–C, C–H, and O–H bond destabilization following bioaccumulation. Moreover, in terms of phytotoxicity evaluation, it was observed that the treated soil, containing both heavy metals and the selected potent bacterial strain, exhibited reduced toxicity, resulting in improved germination and growth parameters for the seeds of Solanum lycopersicum (tomato plant). Overall, the selected bacterial strain demonstrated its potential for effectively removing multiple metals from the metal contaminated environment.